Pengembangan Pangan Lokal Nugget Dali horbo Terhadap Daya Terima dan Kandungan Zat Gizi sebagai Makanan Tambahan Balita Stunting: Development of Local Food Nugget Dali Horbo on Acceptability and Nutritional Content as a Supplementary Food for Stunted Toddlers - Erli Mutiara; Edy Marjuang Purba; Fatma Tresno Ingtyas; Siti Sutanti; Agustina Dalimunthe; Ajeng Inggit Anugerah (Universitas Airlangga, 2025)
Background: Stunting is a condition of impaired growth and development in children under five years of age, resulting from chronic inadequate nutrient intake and recurrent infections, and is characterized by height-for-age below the standard reference. Nutritional improvement efforts for stunted toddlers commonly include the provision of supplementary foods. One potential locally based food product is chicken nuggets enriched with dali horbo. Dali horbo is a traditional Batak fermented food made from buffalo milk, which is rich in fat, protein, and carbohydrates and contains lactic acid bacteria. Objectives: This study aimed to determine the optimal formulation of chicken nuggets substituted with dali horbo based on organoleptic evaluation and proximate nutrient composition. Methods: A Completely Randomized Design was applied using mixtures of chicken meat and dali horbo with three formulations: A (70% chicken meat: 30% dali horbo), B (60% chicken meat: 40% dali horbo), and C (50% chicken meat: 50% dali horbo). The best formulation from the organoleptic test was subsequently subjected to physical and chemical property analyses. Results: The most preferred formulation for supplementary food for stunted toddlers was formulation C (50% chicken meat: 50% dali horbo). Proximate analysis of the selected product showed moisture content of 47.03%, ash 1.88%, protein 10.60%, fat 22.99%, and carbohydrate 17.49%. The nutrient profile met the Indonesian National Standard (SNI) for nuggets, except for fat content, which exceeded the SNI limit. Conclusions: Dali horbo nuggets may be used as a supplementary food intervention for stunted toddlers.